Motivational experiments and activities for high school chemistry - Minoza, Aurora Casumbal 1938-
This study gives motivational experiments and activities which teachers can use in teaching the major topics and concepts normally taken in a high school chemistry course. The experiments and activities included in this paper have been selected based on the following criteria: relevance to a principle or concept, availability of materials needed, results that puzzle or attract attention, ease and speed when performed, and safety.
Thesis (M.A.T.)--University of the Philippines
Keywords: Chemistry -- Study and teaching (Secondary).; Motivation in education